(untitled) (LACCEI, 2024)
In our society, there is currently a constant struggle for equal rights, opportunities, and improvement of the quality of life of people with disabilities. Students with hearing disabilities present communication and learning problems when they attend educational institutions, because they do not have the technological tools that adapt to their needs. In addition, there is a greater technological development motivated by the search for solutions to problems present in educational services. The main objective of this article is to investigate by means of a literary review, the different technological alternatives that exist for people who use sign language as a means of communication and its influence of information technologies for development and learning in an educational field.